The Effect of Learning Experimental Method Toward Learning Writing Ability of Creative Poetry Based on Personal Experience of Seventh Grade Students of SMP Pembina of Palembang - Dessy Wardiah (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis study aims to determine and describe the influence model experiential learning to creative poetry writing ability based on personal experience of the seventh grade students of SMP Pembina Palembang. The method used in this study is an experimental method with a pretest-postes control group design. Samples are 39 students of VII.1 class as an experimental class and VII.4 class wich consist of 34 student as the control class. Technique for collecting data used in this study was the written test. The results of study was there is significant influence of experiental learning method toward students ability in writing creative poetry based on personal experience of seventh grade students of SMP Pembina Palembang. The result of t-tests showed that the value of t-obtained was higher than t-table (2,95 higher than 1,66)Keywords : Learning, Model of Experiental Learning, Writing Poetry, Personal Experience